Character Development Model for Kindergarten Students Based on the Pancasila Student Profile Strengthening Project (P5) in Mataram, Indonesia - Arifamahira, Yumna; Rahmania Octaviani, Windy; Rosmalia, Afina; Wike Pratamaswari, Baiq; Saswari Aji, Bq. Ulan; Sumardi, Lalu (Lafadz Jaya Publisher, 2024)
The importance of character education in early childhood cannot be ignored because this phase is the